Membangun Kesadaran Digital: Sosialisasi Hak dan Kewajiban dalam Penggunaan Media Sosial di SMA 1 Yapis Merauke - Dyana Hesti Kamila; Roro Anggi Sukmawati; Syadila Ainun Nisa; Yulidiana Zesa Azis; Poetri Enindah Suradinata; Zegovia Parera; Nasri Wijaya; Ahmad Ali Muddin; Anton Johanis Silubun (Astha Grafika, 2025)
In the era of globalization, social media has become the main communication tool that affects people's lives, especially teenagers. The community service activity entitled